Pengaruh Penerapan Model Scientific Critical Thinking Berbantuan Exelearning dalam pembelajaran Hukum Dasar Kimia terhadap Self-Efficacy Peserta Didik - Setiawan, Dimas; Rusmansyah; Kusasi, Muhammad (LPPM Universitas Negeri Jakarta, 2024)
This study was conducted to determine the effect of applying the Scientific Critical Thinking (SCT) model assisted by Exelearning in learning the basic laws of chemistry on the self-efficacy of students at SMA Negeri 5 Banjarmasin. This type of research is a pseudo experiment, consisting of an experimental class (SCT model) and a control class (discovery learning model). The samples of this study were class X-E (experimental class) and class X-I (control class) with a total of 60 students. The research data were analyzed descriptively and inferentially. The results showed that there were differences in students' self-efficacy between the experimental and control classes. Thus it is known that the Scientific Critical Thinking model assisted by Exelearning in learning basic laws of chemistry has a positive effect on students' self-efficacy